(3GdYhdeI h CHYGOgG GdGbJUGOjI (B/s - (3YHO GdeLjO, CSYOs; (3GdhGOj, eMehO MSf hCNQhfs ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2011)
(3GdYhdeI h CKQgG Ydi GbJUGOjGJ GdOhd GdYQHjI aj Xd GdJcJdGJ GdQGgfI , BKGQ GdYhdeI Ydi GdGbJUGOjGJ GdYQHjI h GgejI GdJcGed GdGbJUGOj aj ehGLgI BKGQgG GdSdHjI , GdYhdeI h GecGfjGJ GfOeGL GdHdOGf GdYQHjI aj GdGbJUGO GdYGdej , GdHYO GdGbJUGOj ddYhdeI h eOi GecGfjGJ GfNQGW GdOhd GdYQHjI aj GdMOGKI GdJcfhdhLjI , GdGSJKeGQ GdGLfHj GdeHGTQ h BKGQg Ydi GdOhd GdfGejI aj Xd GdHjFI GdOhdjI GdLOjOI , GdJhbYGJ GdeMJedI ddYhdeI Ydi GdbWGY GdeUQaj dOhdI GdchjJ , JMOjGJ GdYhdeI h NjGQGJ GdGSJLGHI (B: (3JMdjd GJLGgGJ GdJMQQ GdeGdj GJLGg GdGSJKeGQGJ GdCLfHjI , GdJehjd GdOhdj aj Xd GdGJLGg fMh GdYhdeI , OhQ GdeUGQa GdGSdGejI aj GdMO ef GdBKGQ GddHjI ddYhdeI , GdJcGed GdGbdjej GdGbJUGOj GdYQHj h JMOjGJ GdYhdeI , GdhMOI GdGbJUGOjI GdeZGQHjI VQhQI eSJYLdI CeGe GdYhdeI , GdJYGhf GdGbJUGOj GdYQHj aj ejOGf GdJLGQI h BaGb JWhQg aj Xd GdYhdeI , eaghe h CSHGH h BKGQ GdYhdeI Ydi GdJLGQI GdNGQLjI ddOhd GdYQHjI , GdYhdeI h JCKjQgG Ydi GdeYGjjQ GdeMGSHjI GdOhdjI h GfYcGSGJgG Ydi GdJWHjbGJ GdeMGSHjI aj GdOhd GdfGejI , bjGS GdGOQGc deYjGQ QSedI JcGdja GdGbJQGV h eOi JWHjbg aj GdTQcGJ GdUfGYjI GdeSGgeI GdYGeI GdGQOfjI, GSJQGJjLjI GdJaGhV eY efXeI GdJLGQI GdYGdejI , GdYhdeI GdeSDhdjI GdchfjI h GdJYGhf GdGbJUGOj GdYQHj h GdGSdGej aj Xd GdYhdeI , GdNUNUI aj Xd eJWdHGJ GdYhdeI , GdBKGQ GdGbJUGOjI ddNUNUI aj Xd GdhdeI eY GTGQI Gdi JQLeI GdCQOf , GdYhdeI h GfYcGSGJgG Ydi YedjI GdJfejI aj GdOhd GdYQHjI , GdShb GdYQHjI GdeTJQcI h GdJMOjGJ GdQGgfI , aLhI GdYde h GdJbGfI aj ehGLgI GdYhdeI h GdfTGW GdEFJeGfj GdYQHj Hjf JOGYjGJ GdeGVj h HYV JMOjGJ GdeSJbHds
Keywords: (3GdGSJKeGQs; (3GdGbJUGO GdOhdjs; (3GdYhdeIs